'Hang on a Tick' – Are Ticks Really the Vectors for Australian Trypanosomes?. Issue 8 (August 2019) - Krige, Anna-Sheree; Thompson, R.C. Andrew; Clode, Peta L.
Abstract : Trypanosomes are global blood parasites that infect a wide range of vertebrate hosts. Several species of Trypanosoma cause disease in humans and domesticated animals, and the majority are transmitted between hosts by haematophagous invertebrate vectors. Ticks have long been speculated as vectors for Australian trypanosomes. Recent studies using advanced molecular techniques have refocused attention on these arthropods, and whilst they have renewed discussions about Trypanosoma species and their vectors, these reports have simultaneously led to premature conclusions concerning the role of ticks as vectors. Here the controversy surrounding ticks as trypanosome vectors is discussed. We highlight the unanswered questions concerning the role played by ticks in trypanosome transmission and suggest future approaches to resolving these key knowledge gaps. Highlights: Trypanosomes (genus Trypanosoma ) are blood-borne protozoan parasites of vertebrates that typically require a haematophagous invertebrate as a vector. Triatomine bugs and several biting flies are recognized as their main vectors. Ticks, as blood feeders, are predisposed to the ingestion of various parasites during feeding and have therefore long been proposed as vectors for Trypanosoma species. Trypanosomes are reported in Australian wildlife, and early indications suggest that some species may adversely affect the health of native hosts. The vectors responsible for transmitting Australian Trypanosoma species between vertebrate hosts are unknown. Ticks are suggested as vectors for several Australian trypanosomes based on microscopic and molecular detection of trypanosomes in ticks removed from wildlife. However, there are no experimental transmission studies to support this hypothesis to date.